Profile of Chicken Nugget Fatty Acid Added Soybean Flour as Food Sources Dietary Fiber - Sondakh, Erwin Hubert Barton; Kalele, Jerry; Ratulangi, Friets; Palar, Conny; Sompie, Meity (PT FORMOSA CENDEKIA GLOBAL, 2024)
The current research were conducted with the aim to determine the effect of soybean flour as fortification ingredient to increase dietary fiber products to chicken nuggets. The meat used for nuggets chicken was taken from the chest. Soybeans were used as a fortification ingredient for the product of chicken nuggets. This experiment use a completely randomized design with five treatments consisting of a treatment: R0 level 0% of soybean of the meat composition of 500 g (0 g of soybean and 500 g of meat), R1 level of 5% of soybean of the meat composition (25 g soybean and 475 g of meat) R2 level of 10% of soy bean of the meat composition (50 g of soybean and 450 g of meat), R3 15% of soybean of the meat composition (75 g of soybean and 425 g of meat), R4 level 20% soybean of the meat composition (100 g of soybean and 400 g of meat). Each treatment was conducted four replications. The results were analyzed using analysis of variance and when there was a difference of average, the DMRT test was used to separate the difference. The results showed that fortification with soybeans in chicken meat had a significant effect on the protein, fat and fatty acid. In conclusion, Product of chicken nuggets using soybean flour can increase unsaturated fatty acids with a composition level of 75 g soybean flour and 425 g chicken meat.